2020
DOI: 10.1039/c9ra10405d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mixed agro-residues (corn crop waste) on lignin-degrading enzyme activities, growth, and quality ofLentinula edodes

Abstract: Using agro-residues in bioreactors to produce mushrooms is an important component of eco-agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 33 publications
0
21
0
2
Order By: Relevance
“…In recent years, many types of agricultural and forestry wastes, including CC, corn straw, old and asparagus stalks, as well as landll items, such as used diapers and food, have been used as mushroom substrates 8,10,26,28 Our results demonstrated that NPC could be used as the main substrate for P. abieticola cultivation.…”
Section: Statistical Analysesmentioning
confidence: 63%
“…In recent years, many types of agricultural and forestry wastes, including CC, corn straw, old and asparagus stalks, as well as landll items, such as used diapers and food, have been used as mushroom substrates 8,10,26,28 Our results demonstrated that NPC could be used as the main substrate for P. abieticola cultivation.…”
Section: Statistical Analysesmentioning
confidence: 63%
“…Different extracellular enzyme activities of fungi can cause different decomposition and utilization of lignin, cellulose, and hemicellulose in plant cell wall (An et al 2015). Laccase is a ligninolytic enzyme and is necessary for lignin degradation by white-rot fungi, such as Lentinus edodes, Pleurotus ostreatus, Ganoderma lucidum, Trametes versicolor, and L. crinitus (Elisashvili et al 2008;Kuhar et al 2015;Han et al 2020b;Serbent et al 2020;Xu et al 2020). The laccase secretion capacity of different white-rot fungi was significantly different.…”
Section: Production Of Laccase From Different Fungimentioning
confidence: 99%
“…Lignocellulosic biomass, versatile and most abundant natural renewable resources, have attracted more attention and considerable interest due to their abilities to convert into green second-generation energy fuels and valued industrial chemicals via the various bio-treatment process of lignocellulosic biomass (Haldar et al, 2016;Pinar et al, 2017;An et al, 2020b;Gaikwad and Meshram, 2020). Using various lignocellulosic wastes, such as corncob, cottonseed hull, bamboos, coffee shell, and tree leaves, to produce enzymes (especially laccase) had been widely investigated in recent years due to the low-cost and vast amounts of lignocellulosic wastes (Lizardi-Jimenez et al, 2019;Thamvithayakorn et al, 2019;Wang et al, 2019;Agrawal and Verma, 2020;Atilano-Camino et al, 2020;Pinheiro et al, 2020;Xu et al, 2020). Laccase (EC 1.10.3.2, p-benzenediol: oxygen oxidoreductase) belongs to a family of copper oxidases and widely distributes in various higher plants, fungi, bacteria, and some insects (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of using two or three white-rot fungi combined with each other to produce laccase was rarely investigated ( Kuhar et al, 2015 ; Vibha and Negi, 2018 ). Most studies had used only one lignocellulosic material to explore the effect on laccase secreted by fungi, and very few had considered using a mixture of two lignocellulosic materials to explore the effect on laccase secretion by fungi ( Lallawmsanga, Leo et al, 2019 ; Thamvithayakorn et al, 2019 ; Unuofin et al, 2019b ; Gaikwad and Meshram, 2020 ; Xu et al, 2020 ). However, evaluation of laccase activities from C. unicolor , Lenzites betulinus , and Schizophyllum sp.…”
Section: Introductionmentioning
confidence: 99%